1989
DOI: 10.1063/1.342720
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectra of SixGe1−x alloys

Abstract: We report pseudodielectric functions of SixGe1−x alloys at room temperature, measured ellipsometrically on polycrystalline samples and single-crystal epitaxial layers, in the 1.7–5.6 eV range. Accurate values of the E1 threshold energies are obtained from numerically differentiated spectra. The measured dependence of E1 on x provides an efficient way to determine the alloy composition x. The spectral and compositional dependence of the optical constants forms a data base for optical studies of Si/SiGe layered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
3
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 257 publications
(117 citation statements)
references
References 12 publications
8
97
3
9
Order By: Relevance
“…3 we compare our calculated LDA+U SIC absorption coefficient with measured absorption by Humlicek et al [19]. Overall, we find a very good qualitative agreement between the calculated and the measured results.…”
Section: Fig 1: the Band-gap Energies Of Si 1−x Ge X At γ-L And ∆-Psupporting
confidence: 64%
“…3 we compare our calculated LDA+U SIC absorption coefficient with measured absorption by Humlicek et al [19]. Overall, we find a very good qualitative agreement between the calculated and the measured results.…”
Section: Fig 1: the Band-gap Energies Of Si 1−x Ge X At γ-L And ∆-Psupporting
confidence: 64%
“…While the broadening and reduction in amplitude is consistent with previous studies of doped GaAs, these works revealed a red shifting of both the E 1 and E 1 + ∆ 1 transitions, whereas we observe a blue shifting. 32 Additionally, in Ga 1−x Mn x As the two peaks appear to merge. As we discuss in sec.…”
Section: B Modeling the Optical Constantsmentioning
confidence: 97%
“…In quenching, the excitation energy of the fluorophore is transferred to electronic excitations in the metal, which are then dissipated via Ohmic loss processes. Thus, the quenching efficiency is ultimately proportional to the imaginary part of the dielectric function, which, for metals, can be relatively large, yet for dielectrics can be very nearly zero: at 600 nm, the imaginary part of the dielectric function is 1.366 for Au [46], [47], 0.104 for Si [48], [49], and zero for crystalline SiO 2 (quartz) [47]. The quenching efficiency is also dependent on the geometry of the tip [39].…”
Section: B Fluorescence Reductionmentioning
confidence: 99%